ALAT MUSIK TRADISIONAL BARDAH DALAM KEHIDUPAN MASYARAKAT MELAYU DI KAMPUNG BUATAN II, KECAMATAN KOTO GASIB, KABUPATEN SIAK - Putri Amelia; Isjoni '; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The instrument is an instrument that is created or modified for the purpose of generating music. Musical instrument composed of various types of them is a traditional musical instrument. One is the traditional musical instrument Bardah in Kampung Artificial II, District Koto Gasib, Siak. This study aims to determine (1) the origin of traditional musical instruments Bardah. (2) the condition of traditional musical instruments Bardah now (3) the role of traditional musical instruments Bardah among the Malays in Kampung Artificial II District Koto Gasib, Siak. (4) the factors supporting and hindering development of traditional musical instruments Bardah in Kampung Artificial II. (5) a driving factor Bardah preservation of traditional musical instruments. (6) the government's attention to the music Bardah. This study uses qualitative research approach to history (History) and data collection techniques such as observation, interviews, documentation and literature. The results showed that Bardah traditional musical instrument is a musical instrument whose existence can not be separated from the Arabs who came to Indonesia. Bardah musical instrument is played also by using an instrument called gong. If the ancients manamainya is "tetawak". Bardah Art is an art that had lost its role among the community of Kampung Artificial II is in the 80s. This art began not turn on again in 1991. In 1992 Bardah art was formed under the name "WISDOM" (Art Association of Traditional Malay). Until now traditional musical instruments Bardah still preserved its existence by the government and the people of Kampung Artificial II, District Koto Gasib, Siak.Keywords: Traditional Musical Instruments, Bardah